Non-Pharmacological Management of Pruritus in Chronic Kidney Disease Patients at Panti Waluya Sawahan Hospital - Perwiraningtyas, Pertiwi; Sutriningsih, Ani; Metrikayanto, Wahyu Dini (Journal of Community Service for Health, 2021)
Patients of chronic kidney disease require long-term hemodialysis therapy. However, this therapy has various complications, one of which is pruritus. Pruritus can interfere with individual activities, cause sleep disturbances, lesions and hyperpigmentation on the skin, to impact the patient's quality of life. So that non-pharmacological management is needed to treat pruritus. The design was cross sectional. The population in this community service was chronic kidney failure patients undergoing hemodialysis therapy in the hemodialysis room. The sample was patients who experience pruritus and undergo hemodialysis therapy at least 1x / week as many as 45 people. The variables were health education related to non-pharmacological management and pruritus. The instruments used leaflets and counseling program units for health education, while for pruritus used the Numeric Rating Scale. The average patient experienced pruritus on a scale of 5, which was a moderate category where itching was felt by frequent scratching. After health education, patients understand how to deal with pruritus with non-pharmacological methods so that the patient's quality of life becomes better